2021
DOI: 10.1016/j.psj.2021.101298
|View full text |Cite
|
Sign up to set email alerts
|

Enteric permeability and inflammation associated with day of hatch Enterobacteriaceae inoculation

Abstract: Early exposure to Enterobacteriaceae may result in inappropriate microbial colonization of the gastrointestinal ( GI ) tract, induce mild GI inflammation, alter immune system development, and predispose poultry to opportunistic infection. Four experiments were conducted to test Enterobacteriaceae isolates Escherichia coli LG strain ( LG ), E. coli Huff strain (Huff), Salmonella Enteritidis LB ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Enterobacteriaceae may lead to inappropriate colonization of gastrointestinal microorganisms, induce gastrointestinal inflammation, alter immune system development, and make the body vulnerable to opportunistic infections. 54 In contrast, intestinal inflammation destroyed the composition of the microbiota, leading to the expansion of Enterobacteriaceae members. 55 Escherichia – Shigella is a member of Enterobacteriaceae and is proportional to the degree of skin itching and positively correlated with most pro-inflammatory factors in mice, 56 but negatively correlated with the integrity of the colonic barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae may lead to inappropriate colonization of gastrointestinal microorganisms, induce gastrointestinal inflammation, alter immune system development, and make the body vulnerable to opportunistic infections. 54 In contrast, intestinal inflammation destroyed the composition of the microbiota, leading to the expansion of Enterobacteriaceae members. 55 Escherichia – Shigella is a member of Enterobacteriaceae and is proportional to the degree of skin itching and positively correlated with most pro-inflammatory factors in mice, 56 but negatively correlated with the integrity of the colonic barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the subclinical dose of APEC, another important consideration is that the birds were not challenged on the first day of their lives, but later, on d 15 or d 50. According to the literature, the youngest birds infected with APEC respond with reduced productivity, although a compensatory growth effect is often observed in later rearing stages ( Chasser et al, 2021 ; Christensen et al, 2021 ). However, despite the fact that APEC infection had no influence on the growth performance of turkeys, its effects were noted in the air sac, and in the enzyme and metabolic activity of cecal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous reports ( 21 23 ), we found that during the first several days posthatch, the diversity of cecal microbiota is very low and composed primarily of Proteobacteria . Exposure of the chicken gut to Enterobacteriaceae at the day of hatch can induce mild, nearly undetectable inflammation leading to immune tolerance of related bacteria, including Salmonella ( 24 26 ). Accordingly, the ceca of chickens infected with STm are only mildly inflamed despite a high bacterial burden.…”
Section: Discussionmentioning
confidence: 99%